In-depth component distribution in electrodeposited alloys and multilayers - László Péter; Kálmán Vad; Attila Csik; Rocío Muñíz; Lara Lobo; Rosario Pereiro; SaÅ¡o Å turm; Kristina Žužek Rožman; György Molnár; Katalin Németh; Katalin Neuróhr; Krisztina Boros; et al. (Journal of Electrochemical Science and Engineering, 2018)
It is shown in this overview that modern composition depth profiling methods like secondary neutral mass spectroscopy (SNMS) and glow-discharge – time-of-flight mass spectrometry (GD-ToFMS) can be used to gain highly specific composition depth profile information on electrodeposited alloys. In some cases, cross-sectional transmission electron microscopy was also used for gaining complementary information; nevertheless, the basic component distribution derived with each method exhibited the same basic features. When applying the reverse sputtering direction to SNMS analysis, the near-substrate composition evolution can be revealed with unprecedented precision. Results are presented for several specific cases of electrodeposited alloys and mulitlayers. It is shown that upon d.c. plating from an unstirred solution, the preferentially deposited metal accumulates in the near-substrate zone, and the steady-state alloy composition sets in at about 150-200 nm deposit thickness only. If there is more than one preferentially deposited metal in the alloy, the accumulation zones of these metals occur in the order of the deposition preference. This accumulation zone can be eliminated by well-controlled hydrodynamic conditions (like the application of rotating disc electrodes) or by pulse plating where the systematic decrease in the duty cycle provides a gradual transition from a graded to a uniform composition depth profile. The application of composition depth profile measurements enabled detecting the coincidence in the occurrence of some components in the deposits down to the impurity level. This was exemplified by the GD-ToFMS measurements of Ni-Cu/Cu multilayers where all detected impurities accumulated in the Cu layer. The wealth of information obtained by these methods provides a much more detailed picture than the results normally obtained with bulk analysis through conventional integral depth profiling and help in the elucidation of the side reactions taking place during the plating processes.